Revisiting Iran through women’s memoirs: alternative narratives from insider within - Zeiny, Esmaeil; Noraini Md Yusof; Talarposhti, Abdolbaghi Rezaei (Penerbit Universiti Kebangsaan Malaysia, 2021)
Life narratives of the Iranian women in the diaspora, which have become very popular in recent years, have long served as a model for understanding Iran for western readers. This popularity is emanated from the curiosity and interest in the west that was raised after 9/11 and the ensuing political aftermath. Written to unveil the lives of Iranian women in the Islamic Republic, these diasporic narratives have been ‘growingly commodified, circulated and consumed uncritically’ in the west. Much ink has been spilled on the surge of diasporic Iranian women’s life narratives, the politics of their reception and circulation in the west, and their liability to furthering imperialist ideologies. We have no intention of continuing the debate over how some of these life narratives facilitate and promote imperialistic agendas. Rather, we would like to embark on an untrodden path, a fascinating journey through the growing body of life narratives by and about Iranian women from inside the Islamic Republic, equipped with accounts that vitiate the orientalist assumptions and diasporic narratives’ generalisations. This paper seeks to introduce and analyse these alternative narratives. By developing a theory of the ‘insider within,’ this paper exhibits how alternative narratives from within can serve as a better model for understanding Iran and Iranian women.